2017
DOI: 10.1159/000484122
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Neural Salty Preference in Obesity

Abstract: Background/Aims: Obesity and high salt intake are major risk factors for hypertension and cardiometabolic diseases. Obese individuals often consume more dietary salt. We aim to examine the neurophysiologic effects underlying obesity-related high salt intake. Methods: A multi-center, random-order, double-blind taste study, SATIETY-1, was conducted in the communities of four cities in China; and an interventional study was also performed in the local community of Chongqing, using brain positron emission tomograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 42 publications
1
25
0
Order By: Relevance
“…Elevated BMI was found to be related to changes in the brain activity in regions involved in salt taste perception [23]. Indeed, it was shown that salt taste engages various brain regions that modulate reward, taste processing, and executive control in eating [64], possibly resulting in greater salt consumption in overweight/obese people, in association with reduced salt sensitivity and a higher salt preference [23,64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated BMI was found to be related to changes in the brain activity in regions involved in salt taste perception [23]. Indeed, it was shown that salt taste engages various brain regions that modulate reward, taste processing, and executive control in eating [64], possibly resulting in greater salt consumption in overweight/obese people, in association with reduced salt sensitivity and a higher salt preference [23,64].…”
Section: Discussionmentioning
confidence: 99%
“…However, study results on this topic are still contradictory and inconclusive. Obese adults were reported to consume more salty foods and to have reduced salt sensitivity and higher salt preference [21][22][23]. Additionally, obese women showed decrease in both olfactory and taste capacity, including salt taste, compared to normal weight women [24].…”
Section: Introductionmentioning
confidence: 99%
“…(38,39) Furthermore, decreased gustatory and olfactory sensitivity are seen, in addition to exacerbated reward responses to food. (40)(41)(42) Individuals with obesity rate energy dense foods as more pleasurable, and foods high in sugar and fat elicit higher reward responses in obese compared to lean individuals. (43)(44)(45) Furthermore, weight gain leads to structural and connectivity changes within the CNS.…”
Section: Beyond Homeostasismentioning
confidence: 99%
“…Furthermore, obese people are prone to an HS intake due to a reduced salt sensitivity and a higher salt preference, contributing to the development of pathologies, such as hypertension (15) . In addition, the consumption of HS diets is related to diastolic dysfunction of the left ventricle in hypertensive and normotensive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…According to the large reports that HS intake increases the risks of hypertension and deaths from CVD, several societies worldwide recommend consumption between 3•75 and 6 g/d; however, daily salt intake is higher than 10 g/d in various regions of the world (13,14) . Recently, Li et al (15) showed that overweight and obese individuals are prone to consuming HS diets, increasing the risk of pathologies such as hypertension. Effects of HS intake in utero and early life on cardiovascular functions have been explored, revealing the deleterious effects of HS on cardiovascular parameters (16,17) .…”
mentioning
confidence: 99%